Biological Performance of Eisenia foetida and Quality of Vermicompost Generated from Dif ferent Organic Sources - Ramos-Remache, Rommel Arturo; Reyes-Pérez, Juan José; Moreno-Vera, Ana Noemí; Llerena-Ramos, Luis Tarquino; Sinchiguano-Briones, Luis Ángel; Espinosa-Palomeque, Bernardo (REVISTA TERRA LATINOAMERICANA, 2025)
The degradation of agricultural soils decreases their fertility and nutrient retention capacity, making the application of organic amendments, such as vermicompost, essential for their restoration and functional improvement. The objective of this study was to evaluate the biological performance of the Californian red worm (Eisenia foetida Sav.) and the quality of the vermicompost generated from four organic substrate mixtures: cattle manure + banana rachis (T1), cattle manure + palm rachis (T2), cattle manure + coconut rachis (T3), and cattle manure + market plant waste (T4), with 50:50 ratios (% by volume). The experimental design used was a randomized block with eight replications. The length, population, growth, and reproduction rates of the red worm were evaluated 30 and 45 days af ter the start of the treatments, in addition to the yield and bromatological quality of the vermicompost produced. The best results were obtained af ter 45 days of evaluation. Treatments T1, T4, and T2 showed the highest average worm lengths, with values of 5.58 ± 0.09, 5.53 ± 0.16, and 5.40 ± 0.25 cm, respectively. Treatment T4 recorded the highest population density, with 4319.75 ± 64.71 worms m³, as well as the highest growth rate (0.32 ± 0.01 mg worm⁻¹ day⁻¹) and the highest reproduction index (14.56 ± 0.23%). Treatment T1 had the highest vermicompost yield, with 40.38±0.58 kg m³, an alkaline pH of 8.77 ± 0.15, and a K content of 1.57 ± 0.01%. However, treatment T3 showed the highest organic matter content (50.97 ± 0.21%), total carbon (22.23 ± 0.99%), and a C/N ratio of 22.61 ±0.70. These results demonstrate the potential of vermicomposting as an ef ficient biotechnological strategy for the reproduction of the Californian red worm and the utilization of agro-industrial organic waste, enabling the production of high-quality organic amendments for the recovery and improvement of agricultural soils.